2016
DOI: 10.1088/1361-6528/aa5378
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of plasma illumination characteristics of few-layer graphene-diamond nanorods hybrid

Abstract: Few-layer graphene (FLG) was catalytically formed on vertically aligned diamond nanorods (DNRs) by a high temperature annealing process. The presence of 4-5 layers of FLG on DNRs was confirmed by transmission electron microscopic studies. It enhances the field electron emission (FEE) behavior of the DNRs. The FLG-DNRs show excellent FEE characteristics with a low turn-on field of 4.21 V μm and a large field enhancement factor of 3480. Moreover, using FLG-DNRs as cathode markedly enhances the plasma illuminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The mechanism of the improvement of the plasma illumination properties and EFE in sp 2 -sp 3 nanocarbon systems was investigated thoroughly by Shankaran et al [144][145][146].…”
Section: Detectors and Light Sourcesmentioning
confidence: 99%
“…The mechanism of the improvement of the plasma illumination properties and EFE in sp 2 -sp 3 nanocarbon systems was investigated thoroughly by Shankaran et al [144][145][146].…”
Section: Detectors and Light Sourcesmentioning
confidence: 99%
“…Interestingly, the PI performance of the NB-DNWs displays substantial improvements as compared to other materials as cathodes in the microplasma device reported earlier (Table ). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the PI lifetime stability of the D-ECNW nanostructures was inspected and it was found that the material can withstand more than 8348 s (139 min) under a tested current density of J PI = 1.0 mA cm −2 (at E = 4000 V cm −1 ), which illustrates the high stability of these D-ECNW nanostructures. This performance of the D-ECNW nanostructures is much better than the microplasma devices which use other types of carbon emitters (carbon nanotubes, CNW, and graphene nanowalls) as the cathode, [60][61][62][63] which signifies that the diamond enhances the PI lifetime stability of these CNW.…”
Section: Plasma Illumination Studies Of Diamond-enhanced Carbon Nanowallsmentioning
confidence: 95%
“…attain high emission of electrons and so are suitable as a cathode for these microplasma devices. [56][57][58][59] But, these cathode materials experience low lifetime stability [60][61][62][63] because the cathodes in the microplasma devices are subjected to continuous plasma ion bombardment during operation. For that reason, a material owning excellent robustness (long lifetime and reliability) and high secondary electron emission efficiency are necessary for acting as a cathode for these microplasma devices.…”
Section: Plasma Illumination Studies Of Diamond-enhanced Carbon Nanowallsmentioning
confidence: 99%